2017
DOI: 10.1002/pssr.201700259
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐Stability of Magnetic Skyrmions in Ultrathin Multilayer Nanodots Induced by Magnetostatic Interaction

Abstract: We report the results of simulations of magnetic skyrmion stability in ultrathin magnetic multilayer nanodots with interfacial Dzyaloshinskii-Moriya exchange interaction (DMI). We found that in presence of the lateral confinement the magnetostatic energy significantly influences the skyrmion stability and leads to stabilization of large radius skyrmion even at low values of the DMI strength, in addition to small radius skyrmion stabilized by DMI. In particular, stabilization of the skyrmion state with two diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
1
18
0
2
Order By: Relevance
“…28 as a function of temperature. The skyrmion bi-stability at zero applied field was simulated recently in thick multilayer dots due to the effect of the dipolar interactions 30 . Importantly, our model also allows us to estimate the energy barrier between the states with the skyrmions of two diameters.…”
Section: Resultsmentioning
confidence: 99%
“…28 as a function of temperature. The skyrmion bi-stability at zero applied field was simulated recently in thick multilayer dots due to the effect of the dipolar interactions 30 . Importantly, our model also allows us to estimate the energy barrier between the states with the skyrmions of two diameters.…”
Section: Resultsmentioning
confidence: 99%
“…However, the magnetostatic interaction increases with the dot thickness increasing and inevitable results in the stabilization of the Bloch skyrmions for relatively small values of the interface DMI. This effect was very recently simulated by Zelent et al [34]. It was shown that increasing the dot thickness the multilayer (Ir/Co/Pt) n dot is in the Bloch skyrmion state for the number of the layer repeats  n 9 if J D <0.5 mJ m −2 or, alternatively, the large-radius Bloch skyrmion state is realized for the single layer Co/Pt dot at J D =0.95 mJ m −2 for the Cothickness >3 nm (the dot radius was 250 nm).…”
Section: Dm Ementioning
confidence: 62%
“…Skyrmions can be stabilized in ultrathin films by the interplay of an external magnetic field, perpendicular anisotropy and the Dzyaloshinskii-Moriya interaction (DMI) that is induced at the interfaces of the ferromagnetic/non-magnetic metal [6]. In the case of multilayer structures, there is additional contribution from the dipolar interactions that leads to the stabilization of stray field skyrmions [7,8]. It was found that confinement due to geometry can increase the stability of the skyrmion significantly [9].…”
Section: Introductionmentioning
confidence: 99%